Sosialisasi Pencegahan Stunting di Dusun Muteran Desa Kejagan, Kecamatan Trowulan, Kabupaten Mojokerto - Firza Farianshah Difandra; Ahmad Yanuar Bahri; Imam Mahmudah; Rinawati Dewi; Yasmine Azalia Wandana; Chaterine Br Tarigan; Hanani Nazua; Cinta Tunggal Rahmadhani; Anggy Kinaya Putri; Sukina Sukina; Yanda Bara Kusuma (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Stunting remains a significant public health challenge in Indonesia, especially in rural areas. The national stunting prevalence was recorded at 24.4% in 2021, still far above the maximum threshold of 14% set in the SDGs for 2024. To tackle this problem, the KKN-T Bela Negara Group 8 team of the National Development University "Veteran" East Java in collaboration with UPT Puskesmas Tawangsari carried out a socialization program on stunting prevention in Muteran Hamlet, Kejagan Village, Trowulan District, Mojokerto Regency on August 2, 2024. This program involved 38 participants of mothers with children under five years old and focused on three main interventions including measuring children's height, weighing children, and giving vitamin A. This activity aims to know how to prevent stunting from various aspects, knowing how to measure and weigh toddlers appropriately according to health procedures and learning how to give vitamin A to children. Through this collaborative effort, it is hoped that the prevalence of stunting in Muteran Hamlet can be significantly reduced so that it can contribute to improving the quality of human resources in the future.